2018
DOI: 10.1534/genetics.117.300574
|View full text |Cite
|
Sign up to set email alerts
|

Mettl3 Mutation Disrupts Gamete Maturation and Reduces Fertility in Zebrafish

Abstract: N-methyladenosine (mA), catalyzed by Mettl3 methyltransferase, is a highly conserved epigenetic modification in eukaryotic messenger RNA (mRNA). Previous studies have implicated mA modification in multiple biological processes, but the function of mA has been difficult to study, because mutants are embryonic lethal in both mammals and plants. In this study, we have used transcription activator-like effector nucleases and generated viable zygotic mutant, Z , in zebrafish. We find that the oocytes in Z adult fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 68 publications
4
68
0
Order By: Relevance
“…This study proves that METTL3 and m 6 A modifications are essential for reproduction in vertebrates (Xia et al, 2018). m 6 A methylation also regulates hematopoietic stem cells development.…”
Section: A Demethylasessupporting
confidence: 63%
“…This study proves that METTL3 and m 6 A modifications are essential for reproduction in vertebrates (Xia et al, 2018). m 6 A methylation also regulates hematopoietic stem cells development.…”
Section: A Demethylasessupporting
confidence: 63%
“…METTL3 was reported to promote the proliferation of ovarian granulosa cells, and another study also confirmed the promotion role in other cell lines; the mechanism may be that METTL3 helps facilitate DNA damage repair (Xiang et al, 2017). Also, knocking out METTL3 prevented the oocytes from maturing (Xia et al, 2018). METTL14 appears to play a supporting role of stabilizing METTL3 and helping to recognise RNA (Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…METTL3 is widely expressed in different tissues in mouse and human, and when knocking-out METTL3 in mouse embryonic stem cells, no traces of m 6 A methylation can be found using mass spectrometry [31]. METTL3 was shown to play a major role in development and function of neural cells [40], cardiac cells [41,42], bone and muscle [43], hematopoiesis [44] and gametogenesis [45,46], as well as in cancer progression [47]. It was also shown in 2015 that it is essential for differentiation in vitro and for mouse development in vivo [31].…”
Section: A "Writers"mentioning
confidence: 99%
“…Loss of YTHDC1 leads to extensive polyadenylation and The first evidence for m 6 A importance during these processes in females was observed in zebrafish, showing that one-third of maternal mRNA is m 6 A-methylated, and its degradation, mediated by YTHDF2 activity, is important for maternal to zygotic transition and timely development of the zebrafish [109]. A later paper on zebrafish showed that loss of METTL3 results in failed gamete maturation and reduced fertility [45]. In mammals as well, YTHDF2 reader protein was the first link found between m 6 A and oogenesis: YTHDF2 is expressed throughout mouse oogenesis, as demonstrated by immunostaining [103].…”
Section: A Role In Oogenesismentioning
confidence: 99%